Penerapan Metode Tilawati dalam Pembelajaran Al-Quran dan Kemampuan Baca Al-Quran Santri di TPQ Darussalam Kepanjen Jombang - Mohammad Saat Ibnu Waqfin (JoEMS (Journal of Education and Management Studies), 2019)
The Tilawati Method is one of the innovations of learning method in reading the Qur'an. Al-Qur'an learning methods that use a balance approach between habituation through classical and truth reading through individuals with reading reading techniques. This method consists of tilawati 1 to 6 and Al-Qur'an from juz 1 to 30. The focus of this research is 1) Describe the method of tilawati used by TPQ Darussalam Kepanjen Jombang 2) Describe the application of the tilawati method by TPQ Darussalam Kepanjen Jombang. This research is a type of field research that is descriptive qualitative, by taking research locations in TPQ Darussalam Kepanjen Jombang. Data collection is done by observation, interview and documentation techniques. Analysis of the data used are 1) Reducing the data. 2) Data display. 3) Drawing conclusions and verification. The results of the study of the application of the method of tilawati in learning to read the Qur'an showed that there was a merging of the classical approach with the visual aids and the individual approach with reading in balance with the book. There is collaboration between the Tilawati curriculum and the TPQ Darussalam local content curriculum, so there is added value in its implementation which results in many students graduating with good grades. Although there are obstacles in terms of class management and time management, as well as human resources who have not yet joined Tilawati, there is anticipation from the TPQ in the form of routine coaching every week